2015
DOI: 10.1159/000369772
|View full text |Cite
|
Sign up to set email alerts
|

Direct Diagnosis of <b><i>Trichomonas vaginalis</i></b> Infection on Archived Pap Smears Using Nested PCR

Abstract: Objectives: Little information is available concerning PCR-based direct detection of Trichomonas infections on archived Pap (Papanicolaou)-stained smears. This study investigates DNA extraction and amplification from archived Pap smears. Trichomonas vaginalis is a parasitic protozoan that infects the urogenital tract of women. Study Design: DNA from archived Pap-stained smears was successfully amplified using the nested PCR to investigate if it could be used for accurate detection and retrospective epidemiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
4
1
Order By: Relevance
“…This percentage was obtained by serology. 19 The frequency observed in pregnant patients in our population is higher than previously reported in Mexico.…”
Section: Discussioncontrasting
confidence: 65%
“…This percentage was obtained by serology. 19 The frequency observed in pregnant patients in our population is higher than previously reported in Mexico.…”
Section: Discussioncontrasting
confidence: 65%
“…T. vaginalis grows best at alkaline environment and attaches itself by its axostyle thus creating the irritation, inflammation, and other symptoms associated with the infection by this parasite [24]. Although our result agreed with those of [25] who found that T.vaginalis may be found in any type of vaginal discharge .…”
Section: Discussionsupporting
confidence: 84%
“…Then, the supernatant was precipitated with 400 μL of absolute ethanol. Finally, 50 μL sterile distilled water was added to precipitated DNA and stored at 4 °C until it could be tested for P. falciparum DNA [21]. …”
Section: Methodsmentioning
confidence: 99%